Analisis Efektivitas Sosialisasi Riset Statistika terhadap Persepsi Sineas Forum Film Jambi dalam Evaluasi Film: Kajian Empiris dengan Bayesian T-Test: Analysis of the Effectiveness of Statistics Socialization on Filmmakers’ of Forum Film Jambi Perceptions in Film Evaluation: An Empirical Study Using the Bayesian T-Test - Trinata, Ario Surya; Mardhotillah, Bunga; Wijaya, Untung; Hambali, Jhoni Hadi; Sihotang, Wanti Perinduri; Basayarahil, S. Farrel Auqi Baswara; Syahrul, Syahrul (Global Education Journal, 2025)
The world of film initially developed from the personal perspective of its makers. The process of filmmaking, assessing film aspects, and evaluating a film are often carried out subjectively, depending on the experience and perception of each individual. This study aims to determine the effectiveness of socialization of the use of statistics in film evaluation to filmmakers of the Jambi Film Forum (FFJ). This research method uses a quantitative approach. This activity was carried out by distributing a questionnaire containing 15 Likert-scale questions to assess participants' perceptions after the socialization. The collected data were analyzed for reliability using Cronbach's Alpha, which showed a value of 0.795, thus declaring the instrument reliable. Next, the effectiveness of the socialization was tested using the Bayesian Paired Samples T-Test, which produced a Bayes Factor value of 2.018 × 10⁷ with an error rate close to zero. The results of the study indicate very strong evidence to accept the alternative hypothesis that filmmakers' perceptions improved significantly after the socialization. With an average score of 58.7, the majority of respondents agreed with the importance of applying statistics in film evaluation. These findings confirm that the outreach program was effective and had a positive impact on participant acceptance. They also demonstrate that the Bayesian approach can be an appropriate analytical method for evaluating the success of similar activities in the social and educational fields.